(untitled) (Texas Journal of Multidisciplinary Studies, 2026)
This study substantiates the necessity of a scientific approach to identifying talented children in football. The limited effectiveness of traditional selection methods, especially the widespread use of subjective assessments, highlights the need for a comprehensive evaluation system. The research developed a model based on physical attributes, technical skills, psychological traits, intellectual capacity, and anthropometric indicators. The integrated assessment of these criteria enables more objective and accurate selection outcomes. This approach contributes to strengthening the scientific and methodological foundations of selection processes in football schools and sports academies